Prognosis of extended-spectrum-beta-lactamase-producing agents in emphysematous pyelonephritis-results from a large, multicenter series - TANIDIR, YILÖREN; KÜTÜKOĞLU, MEHMET UMUT (My University, 2022)
Background: Emphysematous pyelonephritis (EPN) is a necrotizing infection of the kidney and surrounding tissues with significant mortality. We aimed to assess the clinical factors and their influence on prognosis in patients being managed for EPN with and without ESBL-producing bacteria and to identify if those with EPN due to ESBL infections fared any different. Methods: A retrospective analysis was performed on patients with EPN diagnosis from 22 centers across 11 countries (between 2013 and 2020). Demographics, clinical presentation, biochemical parameters, radiological features, microbiological characteristics, and therapeutic management were assessed. Univariable and multivariable analyses were performed to determine the independent variables associated with ESBL pathogens. A comparison of ESBL and non-ESBL mortality was performed evaluating treatment modality. Results: A total of 570 patients were included. Median (IQR) age was 57 (47-65) years. Among urine cultures, the most common isolated pathogen was Escherichia coli (62.2%). ESBL-producing agents were present in 291/556 urine cultures (52.3%). In multivariable analysis, thrombocytopenia (OR 1.616 95% CI 1.081-2.413, p = 0.019), and Huang-Tseng type 4 (OR 1.948 95% CI 1.005-3.778, p= 0.048) were independent predictors of ESBL pathogens. Patients with Huang-Tseng Scale type 1 had 55% less chance of having ESBL-producing pathogens (OR 1.616 95% CI 1.081-2.413, p = 0.019). Early nephrectomy (OR 2.3, p = 0.029) and delayed nephrectomy (OR 2.4, p = 0.015) were associated with increased mortality in patients with ESBL infections. Conservative/minimally invasive management reported an inverse association with mortality (OR 0.314, p = 0.001). Conclusions: ESBL bacteria in EPN were not significantly associated with mortality in EPN. However, ESBL infections were associated with poor prognosis when patients underwent nephrectomy compared conservative/minimally invasive management.
Keywords: Yaşam Bilimleri; Temel Bilimler; Life Sciences; Natural Sciences; Mikrobiyoloji; Yaşam Bilimleri (LIFE); MICROBIOLOGY; Life Sciences (LIFE); emphysematous pyelonephritis; extended-spectrum beta-lactamases; prognosis; nephrectomy; minimally invasive procedures; URINARY-TRACT-INFECTIONS; ESCHERICHIA-COLI; EPIDEMIOLOGY; RESISTANCE; MANAGEMENT